Proteômica para investigar a congelabilidade do semen bovino - Roncoletta, Marcelo; Morani, Erika da Silva Carvalho; Rodrigues, Lúcia Helena Rodrigues; Francheschini, Paulo Henrique [UNESP] (My University, 2013)
The present study was undertaken the protein composition in 2D-electrophoretic pattern (2DE) of the seminal plasma (SP) can interfere in the semen bull freezability, and if we can use that for predicting semen bull freezability. Samples were obtained of 20 bulls (different breeds) with a minimum of 3 years history semen production in commercial semen collection Center. All animals ranged between 2 - 7 years of age. The semen freezability was calculated by # of thawed and approved ejaculates / # of ejaculates submitted to cryopreservation (after semen evaluation and approved to submitted to freeze). The bulls were divided in 3 groups: HIGH (=>80% ejaculates approved); MEDIUM (>60% and <79% ejaculates approved); LOW (=<59% ejaculates approved); the pattern and criteria were the same used in the routine of the commercial semen Center. 68 gels were carried through by 2DE of SP samples indicated 225 detected spots with protein different amount (VION) comparing. Comparing bull ́s semen freezability and VION of each spot found difference among 2 spots from High and Low, even considering just spots with % of detection frequency bigger than 75%. The taurine bulls demonstrated more homogeneous profile when comparing with zebu bulls, considering number and frequency of appearance of spots. The results showed that proteomics can be a useful tool to predict the semen freezability, but we ́ll need to study better the interactions between sperm membrane, seminal plasma and extender to comprehend better which proteome phenotype interfere positive or negatively in the semen freezability.
Proteomics to investigate bull's semen freezability
Keywords: Cattle; Cryopreservation; Proteins; Seminal plasma